Oscillation of Second-Order Quasilinear Generalized Difference Equations - Srimanju, V.; Khadar Babu, Sk.; Chandrasekar, V. (International Journal of Engineering and Technology, 2018)
Authors present sufficient conditions for the oscillation solutions of the generalized perturbed quasilinear difference equationÂ where , . Examples are illustrates the importance of our results are also included.Â Â